Development from an Islamic Persepective - Khairulyadi, Khairulyadi; Ahmad, Muhammad Yunus (Jurnal Sosiologi USK (Media Pemikiran & Aplikasi), 2017)
The paper is an attempt to present fundamental underlying assumptions of development seen from an Islamic perpective and briefly examines some western approaches to development for comparison purposes. The paper holds that western perspective on development fails to understand the very nature of human as a material and non-material being. In Islamic perpective, however, development is seen as an integrated process within which includes the processes to build up a balanced nature of economic, social, environmental and spritual life. It is purposeful human endeavors intended to bring about real material benefits, visible social advantages, and spiritual satisfactions based on on the principle of unicity of God (Tawhid). Development is thereby a process of triangle-relations; the relations between human and God, human and human, and human and nature (environment).Keywords; Development, Islamic, perspective,